Comparison of Markowitz Model and Sharpe Model to Cryptocurrency Investment Measurement - Rifan Fauzi Salasi; , Herry Subagyo; Ana Kadarningsih; Suhita Whini Setyahuni (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Analyzes focuses om the differences between Markowitz and Sharpe models in optimizing cryptocurrency investment portfolios. Data consists of monthly prices from ten major cryptocurrencies collected between January 2022 and December 2024. Markowitz and Sharpe models construct optimal portfolios, which are then evaluated using Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha to measure portfolio performance based on risk and return. Sharpe Portfolio has a higher Sharpe Ratio than Markowitz Portfolio because expected return is higher even though standard deviation is also higher. In Treynor Ratio, both portfolios have similar values because beta is the same, making expected return the key factor in the difference. In Jensen’s Alpha, both portfolios generate returns above market expectations after adjusting for risk, with Sharpe Portfolio achieving a higher value than Markowitz Portfolio. Different portfolio optimization methods result in different risk and return characteristics. Investors can choose a portfolio based on risk preferences. If return-to-total-risk ratio is the main priority, Sharpe Portfolio can be selected due to a higher Sharpe Ratio. However, if risk stability and diversification are more important, Markowitz Portfolio can be an alternative, as it focuses on minimizing risk through a balanced asset combination.